Why Dutch officials take bribes: a toxic mix of factors - Gorsira, Madelijne (Crime, law and social change, 2021)
The aim of this study was to gain an in-depth understanding of the factors that underlie public officials’ engagement in corruption. Given the significant public interest, we gained permission from the Dutch Ministry of Justice to analyze multiple confidential criminal files of cases in which Dutch public officials took bribes from private companies. Extending previous research, we analyzed three types of factors, individual factors, organizational factors, and factors related to the relationships between corrupt officials and their bribers. Moreover, for the first time, we considered the interplay between these three types of factors. The results suggest that public officials’ engagement in bribery is rooted in a combination of individual, organizational and relationship variables that influence and reinforce each other, creating a toxic mix. This implies that the battle against bribery can be fought on multiple fronts, whereby changing one critical factor may cause the mix to lose its toxicity.